Study of Space Requirements for the Specialist Orthopedic Hospital in South Surabaya - Anak Agung Anasthasia Hadi; Intan Kusumaningayu; Joko Santoso (Kirana Publisher (KNPub), 2026)
South Surabaya is an area with a high level of mobility, which is directly proportional to the increasing risk of traffic accidents and bone fractures. The limitations of local facilities cause patients to be referred to the city center, triggering delays in treatment and reducing the effectiveness of recovery. This study aims to examine the functions and space requirements of the Bone Specialist Hospital in South Surabaya as a basis for planning facilities that meet standards. A descriptive qualitative method is used through literature studies, analysis of Ministry of Health regulations, and hospital benchmarking. The study results indicate that this facility requires a strictly structured spatial zoning. These zones must specifically separate emergency services, outpatient care, inpatient care, medical rehabilitation, as well as medical and non-medical support areas. Proper zoning planning and circulation flow are expected to provide optimal, effective, and integrated trauma services and enhance patient safety in the South Surabaya area.